Feminist Accused of Difference from the Self - Harrison, Mary J. (Atlantis, 2016)
In this article, I read Cynthia G. Franklin’s (2009) discussion of Jane Gallop’s (1997) Feminist Accused of Sexual Harassment, arguing that Franklin’s criticism is rooted in disavowed identification. Next, I explore Gallop’s memoir as generating such strong reactions as Franklin’s because it describes the intense and originating conflict of separating from one’s mother to develop a mind of one’s own. I conclude by analysing my own identifications with Gallop and her text.